Lysozyme promotes renal fibrosis through the JAK/STAT3 signal pathway in diabetic nephropathy - Yan Ren; Mengjie Yu; Danna Zheng; Wenfeng He; Juan Jin (Archives of Medical Science, 2023)
Introduction Diabetic nephropathy (DN) is a leading cause of kidney failure. Lysozyme (LYZ) is an essential component of innate immunity and exhibits antibacterial properties. However, LYZ has been reported to induce nephropathy, implying a possible association between impaired renal function and lysozyme expression.